TUBERCULOSIS INCIDENCE IN SAMARA REGION - R. S. Kuznetsova (Туберкулез и болезни лёгких)
The goal of the study is to analyze the incidence of tuberculosis in the population of Samara Region, its changes and trends.Subjects and methods. The data on tuberculosis incidence in the population for 2000-2014 were analyzed, the data were provided by Samara Regional Rospotrebnadzor Directorate. Microsoft Excel was used for data visualization and ArcView 10.0 was used for mapping.Results. According to the performed analysis, tuberculosis incidence was growing in Samara Region, while in theRussian Federation the average rate was going down. Every year, the incidence among rural population exceeds the average long-term rate for the whole region. The part of notified cases of respiratory tuberculosis makes 93-97%. Three municipal regions, Bezenchuksky, Elkhovsky, and Koshkinsky, had the highest burden of respiratory tuberculosis. For many years, these regions have the highest incidence with a high portion of tuberculosis with a positive result of sputum test. Among towns in the region, Chapaevsk differed markedly with its high incidence of tuberculosis. From 2005 tuberculosis incidence in children has been gowning down. Every year the number of tuberculosis cases with multiple drug resistance and HIV co-infection is increasing.